Cohesive stress transfer and shear capacity enhancements in hybrid steel and macro-polypropylene fiber reinforced concrete. (October 2019) - Gali, Sahith; Subramaniam, Kolluru V.L.
Highlights: Multi-linear stress-crack separation (σ-w) relationship of fiber reinforced concrete obtained. Hybrid fiber blend exhibits higher resistance at small crack separation when compared to steel fiber composite. In shear response, the crack opening displacement produced by slip was directly measured from shear crack. Cohesive crack closing stress provides crack control and increase contact stress on primary shear crack faces. Increased resistance at small crack opening in hybrid leads to increased interface stress transfer across the shear crack. Abstract: The link between the fracture behavior and shear capacity of fiber reinforced concrete composite is investigated. The synergy between hooked steel fibers and continuously embossed macro-synthetic fibers in providing improved fracture and post-cracking shear resistance is experimentally evaluated. The fracture responses of plain concrete, concrete with discrete hooked ended steel fibers at two volume fractions (0.5% and 0.75%) and concrete with hybrid blend of steel and macro-synthetic polypropylene fiber (0.3% steel and 0.2% macro-synthetic) are evaluated. The cohesive stress-crack separation relationships of the different composites are obtained from the fracture test responses of notched beams in flexure. There is an improvement in the early fracture response of concrete containing hybrid fiber blend when compared with steel fiber reinforcement, which is due to the higher crack closing stresses produced at small crack openings immediately after cracking. The load carrying capacity in shear obtained from the concrete composite with hybrid blend is significantly higher than the concrete with steel fiber reinforcement at identical fiber volume fraction and is identical to the response obtained from steel fiber composite with a higher volume fraction of fibers. From the full-field displacements obtained using digital image correlation (DIC), the in-situ dilatant behavior of the shear crack is established. Influence of the high early crack opening resistance seen in blends provides better crack control for the shear crack and leads to a significant improvement in the shear resistance derived from stress transfer across the rough crack faces. A mechanistic model for predicting the shear capacity of reinforced fiber composite beams, which considers the crack profile information of the shear crack obtained from DIC and the cohesive stress-crack separation relationship obtained from the fracture tests is presented. The model predicts an increase in the contact stresses on the crack faces in the fiber-reinforced composite with the inclusion of fibers, which increases the shear transfer capacity of the crack.